Instrumental and Integrative Orientations in Second Language Learning among Sudanese Students - Adil Ishag (Vision: Journal for Language and Foreign Language Learning, 2021)
Motivation is one of the most influential factors in second/ foreign language learning. It has been traditionally classified into two types, namely instrumental motivation and integrative motivation. The latter has been claimed to have a more positive impact on the language learning process than instrumental orientations. This study sought to investigate the nature of motivational orientations among Sudanese learners of English and German. The study involved 221 Sudanese undergraduate students studying English and German, respectively. The results of the empirical investigation demonstrated that Sudanese students were more instrumentally motivated to learn English in comparison to German. On the other hand, the students in the German department had more positive attitudes towards the German community and culture in comparison to the students of the English department. Gender differences have also been identified in the department of English only, where female students had a significantly higher level of motivation and were rather integratively motivated to learn English than their male counterparts. The study concluded that both instrumental and integrative constructs are complementary and that attention should be shifted towards motivational intensity in language learning.